Tata Ruang Kota Kolonial Di Sanga Sanga - Ulce Oktrivia (Naditira Widya, 2010)
Sanga sanga is a city-characteristic settlement which was established due to the triumph of new sociological-cultural system over the traditional one. The growth of Sanga Sanga very much related to oil mining activity in this area. Industry emerged accompanied with the huge demand on manpower, which was recruited locally or else where. Manpower from outside Kalimantan was either brought by the Dutch or came by one’s own free will in search for available employment in oil exploitation. This circumstance created a variety of ethnicity and thus made Sanga Sanga a multicultural city. Nevertheless, there was a tendency for certain ethnics to claim the need to spatially preserve their cultural identity. Such need was expressed by the development of kampong named after each ethnicity i.e. Kampong Jawa, Kampong Bugis, Kampong Bali, Kampong Pecinan, Kampong Arab, etc. There was also an exclusive settlement for the Dutch. This article discusses the spatial setting of the colonial city of Sanga Sanga based on the ethnic groups once existed then.